As maras e pandillas no Triângulo Norte da América Central e a atuação dos Estados Unidos em seu combate - Correa, Paulo Mortari Araújo [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Maras and pandillas are terms usually employed in El Salvador, Guatemala and Honduras - which jointly comprise the so-called Central America Northern Triangle - with regard to street gangs, whose members are traditionally youngsters (and mostly men) and share a common identity, which can range from the use of specific forms of communication and cultural expression (including slangs, body gestures, tattoos, graffiti on walls and musical rhythms) to the enforcement of rigorous standards of conduct. The expansion of these groups throughout the region, and its accountability for the growth of violence in big cities have been prompting the adoption of not only domestic measures, but also international ones, which consequently involves both Central American authorities and institutions from other countries, such as the United States. Based on this finding, it is questioned, in this research, what the interest of the United States is in combating street gangs out of its borders, considering that this is commonly seen as a public security problem concerning the state in which territory such groups operate. Through the hypothetical-deductive method, and by the consultation with official reports and other American governmental sources - besides the specific literature on gangs in the Northern Triangle and on the recent history and current context of the region -, at least four hypothesis are tested, which refer to the United States possible perception that the gangs I) are (or are willing to be) tied to groups seen as terrorists; II) have a significant participation on the international illicit drug trade, even in collaboration with great cartels of the region; III) are transnational organized crime groups, capable of coordinating crimes on American soil with their peers established there; and that IV) the violence concerning gangs in El Salvador, Guatemala and Honduras feeds migratory fluxes ...

Maras e pandillas são termos usualmente empregados em El Salvador, Guatemala e Honduras - que, juntos, compõem o chamado Triângulo Norte da América Central - em referência a gangues de rua, cujos membros são tradicionalmente jovens (e, em sua maioria, do sexo masculino) e compartilham de uma identidade comum, o que pode incluir desde o uso de formas de comunicação e expressão cultural específicas (entre gírias, gestos corporais, tatuagens, grafites em muros e ritmos musicais) até a aplicação de rigorosas normas de conduta. A expansão desses grupos pela região e sua responsabilização pela escalada da violência nas grandes cidades têm incitado a adoção de medidas não só domésticas, mas, também, internacionais, envolvendo, por conseguinte, tanto autoridades centro-americanas como instituições de outros países, como os Estados Unidos. Com base nessa constatação, questiona-se, nesta pesquisa, qual é o interesse dos Estados Unidos em atuar no combate a gangues de rua fora de suas fronteiras, considerando que isso é comumente visto como um problema de segurança pública do Estado em cujo território tais grupos operam. Através do método hipotético-dedutivo e a partir da consulta a relatórios oficiais e outras fontes do governo estadunidense - além da literatura específica sobre as gangues no Triângulo Norte e sobre a história recente e contexto atual da região -, testam-se ao menos quatro hipóteses, que se referem à possível percepção dos Estados Unidos de que as gangues I) têm ou almejam ter vínculos com grupos tidos como terroristas; II) atuam de forma expressiva no tráfico internacional de drogas, inclusive em cooperação com grandes cartéis da região; III) são grupos transnacionais do crime organizado, capazes de coordenar delitos em solo estadunidense com seus pares lá estabelecidos; e que IV) a violência concernente às gangues em...
Keywords: Gangues - América Central; Violência urbana - América Central; Identidade social - Honduras; Identidade social - Guatemala; Identidade social - El Salvador; Relações internacionais; International relations; America Central - Relações exteriores; Estados Unidos - Relações exteriores